Assessment of carbon footprint at University Technology Malaysia (UTM) - Yazdani, Z. (2013)
This study has been conducted to evaluate the ongoing issue of carbon footprints, and to identify sustainable carbon reduction strategies at the UTM main campus in Skudai, Southern Malaysia. The study focuses on the main contributors to carbon footprint from three emission, categories, specifically transportation, electricity consumed and waste generated. The study will look at the strategies for carbon emission mitigation, using data collected from several units in UTM, namely the Asset and Built Office, Security Office and Residential College, in order to estimate the carbon emissions. The study will also provide some suggestions on strategies for energy management systems to reduce the amount of CO2 emission in UTM. © (2013) Trans Tech Publications, Switzerland.